1985
DOI: 10.1210/endo-116-2-499
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Type of Vasopressin Receptor on Anterior Pituitary Corticotrophs?*

Abstract: Suspensions of rat anterior pituitary cells were exposed to corticotropin-releasing factor (CRF) (5 nM) and various neurohormones (0.002-1000 nM). CRF-induced secretion of ACTH was doubled by 0.1 nM arginine vasopressin (AVP), 0.2 nM arginine vasotocin, 1 nM oxytocin, 10 nM angiotensin II, and 100 nM noradrenalin; vasoactive intestinal peptide had no effect at 0.2-200 nM. CRF potentiation by AVP was also observed at lower concentrations of CRF. Since AVP appeared to be the most potent modulator of CRF-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(58 citation statements)
references
References 28 publications
7
51
0
Order By: Relevance
“…The reason for this variation in affinity of [d(CH2)5Tyr(Me)]AVP is not known, but the possibility of further heterogeneity of vasopressin V1 receptors exists (Vanner et al, 1990). It has been found that the vasopressin VI receptor in the pituitary gland is resistant to antagonism by [d(CH2)5Tyr(Me)2]AVP, (Antoni et al, 1984), and this subtype of vasopressin receptor has been designed as Vib (Jard et al,1986) or V3 (Baertschi & Friedli, 1985 (Katusic et al, 1984;Vanner et al, 1990;Thibonnier et al, 1993), suggesting the presence of contraction-mediating V,-vasopressin receptors in the preparations studied. In contrast, the -log KB values of…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this variation in affinity of [d(CH2)5Tyr(Me)]AVP is not known, but the possibility of further heterogeneity of vasopressin V1 receptors exists (Vanner et al, 1990). It has been found that the vasopressin VI receptor in the pituitary gland is resistant to antagonism by [d(CH2)5Tyr(Me)2]AVP, (Antoni et al, 1984), and this subtype of vasopressin receptor has been designed as Vib (Jard et al,1986) or V3 (Baertschi & Friedli, 1985 (Katusic et al, 1984;Vanner et al, 1990;Thibonnier et al, 1993), suggesting the presence of contraction-mediating V,-vasopressin receptors in the preparations studied. In contrast, the -log KB values of…”
Section: Discussionmentioning
confidence: 99%
“…Although early studies proposed that AVP was the hypothalamic corticotrophin-releasing factor (331), after isolation of CRH from ovine hypothalami (515), this CRH peptide and its rodent and human counterparts proved to be a more powerful ACTH secretagogue than AVP, and it has since been shown to play a major role in the regulation of the HPA axis (7). ACTH secretion of the anterior pituitary induced by AVP is mediated through the V1b receptor (36,252). Two kinds of CRH receptors, CRH-R1 and CRH-R2, have been identified thus far (202).…”
Section: The Hypothalamic-pituitary-adrenal Axismentioning
confidence: 99%
“…Recently, Baertschi and Friedli (1985) reported that anterior pituitary vasopressin receptors resembled but were not identical to V1 (pressor and hepatic), and that they did not resemble V2 (renal) and might be classified as V3 (pituitary) receptors. DpTyr(Me)AVP is an antipressor agonist of AVP and a potent antagonist of the ACTH releasing properties of AVP (Aizawa et al, 1982;Baertschi et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…DpTyr(Me)AVP is an antipressor agonist of AVP and a potent antagonist of the ACTH releasing properties of AVP (Aizawa et al, 1982;Baertschi et al, 1985). Rivier and Vale (1983) reported that pretreatment with dpTyr(Me)AVP partially suppressed the stress- induced ACTH and corticosterone response.…”
Section: Discussionmentioning
confidence: 99%